Sophie's world a novel about the history of philosophy - Gaarder, Jostein 1952- (Farrar, Straus and Giroux, 1994)
The protagonists are Sophie Amundsen, a 14-year-old girl, and Alberto Knox, her philosophy teacher. The novel chronicles their metaphysical relationship as they study Western philosophy from its beginnings to the present. A bestseller in Norway.